Long-Standing Type-2 Diabetes Mellitus Is Related to Neuropathy Incidence: A Cross Sectional Study - Syamsiah; Andi Baso Tombong; Andi Nurlaela Amin (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2021)
Neuropathy has been associated with various risk factors, including increasing age, male gender, poor sugar consumption, lipid value index and blood pressure, duration, and severity among patients with Diabetes Mellitus. In Bulukumba Regency, a report by the Bulukumba District Health Office reveals that there were 5410 visits of Diabetes Mellitus patients. This study aimed to identify the relationship between the long-standing Type-2 Diabetes Mellitus with neuropathy incidence among DM patients at H. Andi Sulthan Daeng Radja Hospital in Bulukumba Regency. This study that was conducted in July - August 2020, used a cross-sectional design. The study involved 38 patients selected by employing the purposive sampling technique. In terms of duration since diagnosed Type-2 DM, there were 30 patients (78.9%) included in the short-period category (1-5 years), and eight people (21.1%) included in the long-period category. The proportion of respondents that experienced an incidence of neuropathy are as follow 5.3% (two patients) with mild neuropathy, 60.5% (23 patients) with moderate neuropathy, and 34.2% (13 patients) with severe neuropathy. Bivariate analysis using Kolmogorov-Smirnov test results in p-value = 0.006 (<α = 0.05). The research concludes that there is a significant relationship between the length of the suffering of Type-2 Diabetes Mellitus and the incidence of neuropathy. It is recommended that Type-2 DM patients should be educated about the risk of developing neuropathy and its associated health consequences. Policies regarding the use and/ or development of neuropathy assessment within healthcare facilities are also encouraged to help healthcare professionals educate such patients to prevent the negative impact of diabetic neuropathy among DM patients in the future.